Pembuatan Aplikasi Panggilan Darurat Berbasis Android Menggunakan Location Based Services - Ardi Wijaya (JSAI (Journal Scientific and Applied Informatics), 2019)
In everyday life we often encounter emergency situations such as accidents, drowning victims, fires, crimes and so on. Certain community may have had socialization or learned how to handle or first aid the emergencies, but not all societies know how to do first aid for emergencies.This research is aimed at building an Android-based emergency call application system for Bengkulu Region so that people can dial important phone numbers and public services when there is a crime or accident. The benefits of this application is as a medium to facilitate users of mobile devices based on Android in making emergency public service calls. From the problems that occur then, the problem of this research is How to Create Android-Based Emergency Call Applications For Bengkulu Region Using Location Based Services. The purpose of this research is to Design and Build Android-Based Emergency Call Applications for Bengkulu Region Using LBS Technology and create easily and quickly Emergency safe Calling System. The place of research is conducted on public service in Bengkulu city and is independently created. Data collection is done by using interview, observation and literature study method. The results showed that Applications that are created can help people to face emergencies so they do not get constrained when looking for agencies contact information that provide assistance services in times of emergency.Keywords :      Applications, Emergency Calls, LBS